Cr < 3 + > activated oxyfluoride near-infrared luminescent material, preparation method thereof and LED device
The fluorine oxide luminescent material AmEnMtSi8O22F2:xCr3+ activated by Cr3+ ions solves the problem of weak absorption of rare earth ion activated phosphors in the blue light band, achieving efficient matching with LED chips and broadband near-infrared light emission, and is suitable for various near-infrared light source fields.
Patent Information
- Application Number
- CN202410507982.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-25
- Publication Date
- 2025-10-28
AI Technical Summary
Existing rare earth ion-activated near-infrared phosphors have weak absorption in the blue light band and are difficult to be compatible with high-performance blue light chips. They also have narrow emission peaks and low absorption efficiency, which limits their practical applications.
The fluorine oxide luminescent material AmEnMtSi8O22F2:xCr3+ activated by Cr3+ ions is synthesized by high-temperature solid-state method. It is suitable for excitation of blue or red LED chips in the range of 300-800nm, emits near-infrared light in the range of 650-1300nm, with a peak value around 880nm and a half-peak width of 160nm.
It achieves effective matching with commercial blue or red LED chips, emits efficient broadband near-infrared light, reduces manufacturing costs, improves luminous efficiency and stability, and is suitable for a variety of near-infrared light source fields.
Smart Images

Figure CN120843087A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of luminescent materials, specifically relating to a Cr... 3+ Activated fluorine oxide near-infrared luminescent materials, their preparation methods, and luminescent devices. Background Technology
[0002] With the rapid development of science and technology, the lighting industry has made revolutionary progress, and solid-state light sources are being applied to more and more fields. Historically, the first commercial lighting technology was the gas lamp, whose underlying principle was the combustion reaction of methane. By adding a rare-earth oxide shroud, the heat energy and ultraviolet radiation of the gas were converted into visible light, providing lighting services for various locations. However, with the popularization of electric lights, incandescent lamps replaced gas lamps in 1879, and fluorescent tubes and compact fluorescent lamps began to be widely used in the 1950s and early 1990s, respectively. From an energy consumption perspective, incandescent lamps generate a large amount of heat when operating; from an environmental perspective, each discarded compact fluorescent lamp pollutes at least 90 tons of water and soil. Therefore, to overcome the shortcomings of traditional light sources, InGaN / GaN blue light-emitting diodes (LEDs) and phosphor-converted LEDs were proposed to gradually replace electric lamps.
[0003] Phosphor-converting LEDs refer to devices in which phosphors are coated onto commercial LED chips. The excitation light emitted by the LED chip is absorbed by the phosphors, exciting ground-state electrons to an excited state, which then transition back to the ground state and emit light of the desired wavelength. For example, a typical method for fabricating white phosphor-converting LEDs involves coating high-efficiency red and green phosphors onto a commercial blue LED chip and then encapsulating it. Broadband near-infrared light sources have wide applications in night vision imaging, non-destructive testing, medical imaging, and information recognition. Among various near-infrared light sources, phosphor-converting broadband near-infrared LEDs (pc-NIR LEDs) are gradually emerging due to their compact structure, low cost, and high efficiency. In recent years, some rare-earth ion-activated near-infrared phosphors have been reported. For example, in 2023, researchers such as Xia et al. designed and synthesized a novel Eu phosphor. 2+ Ion-activated oxide phosphor Sr2LaGaO5:Eu 2+ This phosphor exhibits broadband emission with an emission peak at 618 nm under 450 nm blue light excitation. Further investigation of the phosphor's crystal structure and spectrum revealed that Eu... 2+ The 5d energy level of the ion exhibits significant crystal field splitting in this structure, thus enabling broadband emission. This is achieved by introducing Ba... 2+ The ions, with their large lattice distortion, result in a significant redshift in the emission spectrum (from 618 nm to 800 nm), which provides a basis for exploring novel Eu ions. 2+ Ion-activated near-infrared phosphors offer a new approach. Yang's team successfully synthesized Pr using a high-temperature solid-state reaction method.3+ Ion-activated BiLa2O 4.5 Luminescent material. This phosphor exhibits broadband near-infrared emission with an emission peak exceeding 1300 nm and a full width at half maximum (FWHM) exceeding 140 nm at room temperature.
[0004] However, despite my country's abundant rare earth resources and the diverse emission bands of rare earth ions, which also possess excellent luminescent properties, the high cost of high-purity, high-quality rare earth oxides and the weak absorption of most rare earth ion-activated phosphors in the blue light band make them incompatible with high-performance, technologically mature blue light chips, thus increasing the development cost of high-efficiency LEDs. Furthermore, the ff electron transitions within the same shell (f-shell) of trivalent rare earth ions are parity-forbidden, and the local crystal field of rare earth ions has a very small effect on the emission spectral position. Therefore, the energy levels in the crystal field will exhibit discrete energy levels, resulting in narrow emission peaks and low absorption efficiency in the luminescent material, severely limiting its practical applications. As a key component of broadband near-infrared PC-LEDs, Cr... 3+ Ion-doped phosphors exhibit unique characteristics such as high quantum efficiency, large absorption cross-section, and tunable emission wavelength, and have therefore attracted widespread attention from researchers in recent years.
[0005] As is well known, Cr 3+ Ions have unique 3d 3 The electronic structure and luminescence properties of Cr in the octahedron are easily affected by the local crystal field environment. 3+ The first excited state (lowest excited state) of an ion under a weak crystal field is: 4 T2( 4 F) energy level, while in a strong crystal field environment it is 2 E-level. Electron transitions within a weak crystal field. 4 T2( 4 F)→ 4 A2, therefore exhibiting a longer emission band. Although this transition is parity-forbidden, it generally results in strong and broad spectral bands in both absorption and emission spectra. This is due to the unforbidden parity melody caused by the interaction between electrons and specific lattice vibrational modes. When Cr 3+ As the ion-localized crystal field strength increases, the lowest excited state changes from 4 T2( 4 F) Energy level transformation 2 The E energy level, due to 2 E→ 4 The electronic transitions of A2 are parity- and spin-forbidden. Therefore, when Cr 3+ Ion-activated phosphors typically exhibit narrow-band emission under a strong crystal field. Additionally, 2 The E energy level hardly changes with the crystal field; Cr in a strong crystal field3+ Ions are difficult to spectrally tune. Due to Cr... 3+ Characteristic electronic transitions of ions, such as 4 A2→ 4 T2( 4 F) 4 A2→ 4 T1( 4 F) and 4 A2→ 4 T1( 4 P) etc., Cr 3+ Ion-activated near-infrared phosphors exhibit strong broadband absorption in the near-ultraviolet-visible spectral range. These strong and broad absorption bands indicate that Cr... 3+ Ion-activated near-infrared phosphors can be well matched with commercial blue LED chips. Based on the above design principles, a series of Cr-based near-infrared phosphors have been developed. 3+ A highly efficient near-infrared phosphor for activating ions.
[0006] Although a wide variety of near-infrared phosphors have been developed to date, most luminescent materials struggle to achieve low-energy (>850nm) emission and also face challenges such as low luminous efficiency and poor stability. Therefore, developing a near-infrared phosphor with long-wavelength emission and excellent luminescent performance is of paramount importance. Summary of the Invention
[0007] To address the aforementioned technical problems, this invention provides a near-infrared luminescent material, wherein the chemical composition of the luminescent material is A. m E n M t Si8O 22 F2:xCr 3+ Where A, E, and M are monovalent, divalent, and trivalent metallic elements, respectively, and Cr 3+ The luminescent central ion (doping sites are determined by the specific chemical formula), m, n, and t are the number of atoms in the balanced valence state of that chemical formula (preferably, 0 ≤ m ≤ 14, for example, m = 3; 0 ≤ n ≤ 7, preferably 5 ≤ n ≤ 6, for example, n = 5.40, 5.42, 5.44, 5.45, 5.46, 5.47, 5.48, 5.49; 0 ≤ t ≤ 4.7, preferably 0.01 ≤ t ≤ 1, for example, t = 0.02); x is the activator Cr. 3+ Ion doping level, 0.01 at.% ≤ x ≤ 30 at.%.
[0008] According to an embodiment of the present invention, the luminescent material can be excited by a blue or red LED chip in the range of 300-800nm to emit near-infrared light with a wavelength range of 650-1300nm, a peak value around 880nm, and a half-maximum width at half maximum (FWHM = 160nm).
[0009] According to an embodiment of the present invention, A is selected from one, two or more monovalent metal elements such as Na, K, and Li; E is selected from one, two or more divalent metal elements such as Ca, Mg, Sr, and Ba; and M is selected from one, two or more trivalent elements such as Al, Ga, and Sc.
[0010] According to an embodiment of the present invention, the chemical composition of the luminescent material may be Na3Mg. 5.49 Si8O 22 F2:0.01Cr 3+ Na3Mg 5.48 Si8O 22 F2:0.02Cr 3+ Na3Mg 5.47 Si8O 22 F2:0.03Cr 3+ Na3Mg 5.46 Si8O 22 F2:0.04Cr 3 + Na3Mg 5.44 Si8O 22 F2:0.06Cr 3+ Na3Mg 5.42 Si8O 22 F2:0.08Cr 3+ Na3Mg 5.40 Si8O 22 F2:0.10Cr 3+ Na 2.98 Ca 0.01 Mg 5.44 Al 0.02 Si8O 22 F2:0.03Cr 3+ .
[0011] According to an embodiment of the present invention, the luminescent material is obtained by heat treatment of raw materials including A source, E source, M source, Si source, F source and Cr source.
[0012] This invention also provides a method for preparing the luminescent material, comprising the following steps:
[0013] According to chemical formula A m E n M tSi8O 22 F2:xCr 3+ The stoichiometric ratio of each element in the mixture is determined by mixing the A source, E source, M source, Si source, F source and Cr source, and then heat-treating the mixture to obtain the luminescent material.
[0014] According to an embodiment of the present invention, the A source is provided by a compound containing A ions; for example, it may be selected from one or more of oxides, carbonates, and fluorides containing A ions. According to an embodiment of the present invention, the E source is provided by a compound containing E ions; for example, it may be selected from one or more of oxides, carbonates, and fluorides containing E ions.
[0015] According to an embodiment of the present invention, the M source is provided by a compound containing M ions; for example, it may be selected from one or more of oxides, carbonates and fluorides containing M ions.
[0016] According to an embodiment of the present invention, the Si source is provided by a compound containing Si ions; for example, it may be selected from oxides containing Si ions.
[0017] According to an embodiment of the invention, the F source is provided by a compound containing F ions; for example, it may be a fluoride selected from A, E or M above.
[0018] According to an embodiment of the invention, the Cr source is provided by a compound containing Cr ions; for example, one of Cr2O3, CrF3, or a combination thereof.
[0019] According to an embodiment of the present invention, the mixing method is one or both of dry grinding and wet grinding. The preferred mixing method is to first perform dry grinding (e.g., 1-30 min), and then add anhydrous ethanol for wet grinding for at least 30 min, preferably wet grinding for 30-200 min.
[0020] According to an embodiment of the present invention, the preparation method further includes drying the mixed raw materials. For example, the drying temperature is 180–220°C, exemplarily 200°C; the drying time is 1–5 hours, exemplarily 4 hours. Preferably, after drying, the dried product can also be dry-milled, for example, for 10–200 minutes.
[0021] According to an embodiment of the present invention, the heat treatment is a high-temperature solid-state reaction. Preferably, the heat treatment includes three steps: heating, holding, and cooling, wherein the heating and cooling rates are no higher than 10°C / min, and the holding time is greater than 6 hours. For example, the heating and cooling rates are 1-5°C / min, and the holding time is 10-160 hours (exemplarily, the holding time is 10 hours, and the heating and cooling rate is 4°C / min). The heat treatment employs a two-stage sintering process. The first-stage sintering includes raising the temperature from room temperature to the first-stage sintering temperature at a certain rate (e.g., 1-10°C / min). The first-stage sintering temperature is 400-600°C, exemplarily 500°C; the first-stage sintering time is 1-5 hours, exemplarily 4 hours; the second-stage sintering includes, after the first-stage sintering, raising the temperature from the first-stage sintering temperature to the second-stage sintering temperature at a certain rate (e.g., 1-10°C / min). The secondary sintering temperature is 900-1300℃, with 1100℃ as an example; the secondary sintering time is 4-10 hours, with 6 hours as an example. In this invention, the mixed raw materials undergo drying and preheating, primary sintering pre-firing, and secondary sintering high-temperature calcination. The purpose of preheating and pre-firing is to remove moisture, CO2, etc. from the powder to ensure that the raw materials undergo sufficient solid-phase reaction in the secondary sintering.
[0022] According to an embodiment of the present invention, the preparation method further includes grinding the obtained sintered product (e.g., dry grinding in a mortar for more than 30 minutes) and collecting the luminescent material.
[0023] According to an embodiment of the present invention, the preparation method includes, for example, the following steps:
[0024] (1) According to chemical formula A m E n M t Si8O 22 F2:xCr 3+ The stoichiometric ratios of each element in the mixture are determined, where 0.01 at.% ≤ x ≤ 30 at.%. Compounds containing A ions, E ions, M ions, Si ions, Cr ions, and F ions are weighed separately and ground to obtain a mixed powder.
[0025] (2) The mixed powder obtained in step (1) is subjected to heat treatment to obtain the product;
[0026] (3) The product obtained in step (2) is ground and collected to obtain the luminescent material.
[0027] This invention also provides applications for the above-mentioned luminescent material, which can be used as a near-infrared luminescent material in various fields using near-infrared light sources, such as detection, marking, identification, and optoelectronic devices. It is preferably used in LEDs.
[0028] The present invention also provides an LED device, comprising at least one of the light-emitting materials.
[0029] According to an embodiment of the present invention, the LED device further includes an LED chip, the LED chip being used to carry the aforementioned light-emitting material A. m E n M t Si8O 22 F2:xCr 3+ .
[0030] According to an embodiment of the present invention, the LED chip can be selected from blue LED chips or red LED chips, preferably a 480nm blue LED chip.
[0031] According to an embodiment of the present invention, the LED device is excited by a 300-800nm blue LED chip or a red LED chip, which can obtain near-infrared light with an emission wavelength of 650-1300nm and can be used as a near-infrared light source.
[0032] According to an embodiment of the present invention, the LED device includes an adhesive layer disposed on the LED chip, the adhesive layer containing uniformly dispersed luminescent material A. m E n M t Si8O 22 F2:xCr 3+ The adhesive in the adhesive layer is epoxy resin, polycarbonate, or silicone; silicone is preferred. The amount of adhesive used is not particularly limited; it should be sufficient to ensure uniform application onto the LED chip according to known procedures in the art.
[0033] According to an embodiment of the present invention, the LED device further includes a base, a heat sink, and a lens. The LED chip is fixed on the base by the heat sink, an adhesive layer is coated on the LED chip, and the lens is disposed on the adhesive layer.
[0034] The present invention also provides a method for preparing the above-mentioned LED device, comprising the following steps: mixing the above-mentioned luminescent material with adhesive evenly, and then coating it onto an LED chip.
[0035] The present invention also provides the application of the LED device as a near-infrared light source in the fields of analysis and detection, iris recognition, automotive sensing and security.
[0036] The beneficial effects of this invention are:
[0037] (1) This invention provides a luminescent material A m E n M t Si8O 22 F2:xCr3+ Its main component is Cr 3+ As a luminescent central ion, it can effectively emit near-infrared light of 650-1300nm when excited by light of 300-800nm.
[0038] (2) This invention uses a solid-state method to synthesize luminescent material A m E n M t Si8O 22 F2:xCr 3+ It has the advantages of low raw material cost, simple process, and easy operation, and can easily realize the large-scale preparation of luminescent materials.
[0039] (3) The luminescent material A provided by the present invention m E n M t Si8O 22 F2:xCr 3+ It can be effectively excited by existing commercial blue or red LED chips, packaged into LED devices, and can realize the commercialization of near-infrared LED devices. Attached Figure Description
[0040] Figure 1 In the figure, a, b, c, d, e, f, g, and h are comparison diagrams of the XRD of several different phosphors prepared in Examples 1-8 of this invention and the XRD derived from COD#9001995.
[0041] Figure 2 The excitation and emission spectra of the phosphor prepared in Example 3 of this invention are shown at room temperature.
[0042] Figure 3 In the figure, a, b, c, d, e, f, g, and h are comparison diagrams of the emission spectra of the phosphor samples prepared in Examples 1-8 of the present invention under 470nm blue light excitation.
[0043] Figure 4 This is an example of the application of the phosphor sample prepared in Example 3 of the present invention with a near-infrared LED chip packaged with a blue light chip and non-destructive testing of tissue. Detailed Implementation
[0044] The preparation method of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0046] Examples 1-7: Na3Mg 5.5-x Si8O 22 F2:xCr 3+ Preparation of luminescent materials
[0047] Example 8: Na 2.98 Ca 0.01 Mg 5.44 Al 0.02 Si8O 22 F2:0.03Cr 3+ Preparation of luminescent materials
[0048] Examples 1-8 were synthesized using a high-temperature solid-state method, differing only in the types and amounts of raw materials used. Table 1 lists the types and amounts of raw materials used in Examples 1-8.
[0049] The specific steps of the synthesis are as follows: Weigh the reactants according to the stoichiometric ratio, place them in an agate mortar and grind them thoroughly for 3-5 minutes, then add an appropriate amount of ethanol and grind for 30 minutes. Afterwards, place the mixture in an 80℃ oven to dry for 10 minutes; after cooling to room temperature, remove it and grind it appropriately to remix the powder adhering to the mortar. Collect the powder in a corundum crucible; cover the crucible containing the powder and place it in a 200℃ oven to dry for 4 hours, then allow it to cool naturally to room temperature. Transfer the mixture to an agate mortar and dry grind for 30 minutes. Collect the mixed powder in the corundum crucible, cover it, and then place it in a muffle furnace for pre-firing. The pre-firing temperature is set to increase from room temperature to 500℃ at a heating rate of 4℃ / min, and then... The sample was heated to 00℃ for 4 hours, then cooled to room temperature at a rate of 4℃ / min. The pre-fired powder sample was then removed, placed in an agate mortar, ground for 30 minutes, and then collected and placed in a corundum crucible. After covering, it was transferred to a muffle furnace for sintering. The sintering temperature was set to increase from room temperature to 1100℃ at a rate of 4℃ / min, held at 1100℃ for 6 hours, and then cooled to room temperature at a rate of 4℃ / min (e.g., 4℃ / min). Finally, the sintered phosphor sample was removed, placed in a mortar, ground for 20-30 minutes, and the phosphor was collected.
[0050] Phase analysis of the samples was performed using an X-ray diffractometer, and the spectral characteristics of the samples were measured using an FLS980 (Edinburgh Instruments) fluorescence spectrometer.
[0051] Table 1 Preparation parameters for Examples 1-8
[0052]
[0053] Figure 1 The XRD patterns of samples from Examples 1-8 show that the luminescent material samples synthesized by the high-temperature solid-state method in this invention are all fluorosilicate target phases according to XRD analysis, and they match the card calculated by COD#9001995.
[0054] Figure 2 The excitation spectrum of the phosphor prepared in Example 2 of this invention was obtained at a monitoring wavelength of 880 nm. The results show that the luminescent material prepared in this invention has a broadband excitation peak in the range of 300-800 nm, with the optimal excitation positions located at 470 nm and 670 nm.
[0055] Figure 3 In the figures, a, b, c, d, e, f, g, and h are comparative emission spectra of the phosphor samples prepared in Examples 1-8 of this invention under 470 nm blue light excitation. The results in the figures show that when Cr 3+ The emission intensity of the luminescent material obtained with a doping amount of 3 at.% is higher. Example 8 further incorporates Ca. 2+ and Al 3+ The emission peak position of the luminescent material remains unchanged, but the luminescence intensity of the luminescent material decreases.
[0056] Example 9: Demonstration of LED Device Fabrication and Application
[0057] like Figure 4 As shown, the luminescent material synthesized in Example 3 above is mixed with epoxy resin at a mass ratio of 1:1, coated onto a blue LED chip, and then cured and encapsulated to obtain a near-infrared emitting LED device.
[0058] The near-infrared emitting LED device prepared in this embodiment was used as a near-infrared light source for non-destructive tissue testing, and the results are as follows: Figure 4 As shown in the figure, the results demonstrate that a near-infrared emitting LED device made using the luminescent material of this invention can obtain a clear image of blood vessels in the palm as a near-infrared light source.
[0059] The above embodiments illustrate the implementation of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A near-infrared luminescent material, characterized in that, The chemical composition of the luminescent material is A. m E n M t Si8O 22 F2:xCr 3 + A, E, and M are monovalent, divalent, and trivalent metallic elements, respectively, and Cr is... 3+ The luminescent central ion is , where m, n, and t are the number of atoms in the balanced valence state of the chemical formula (preferably, 0 ≤ m ≤ 14; 0 ≤ n ≤ 7; 0 ≤ t ≤ 4.7); x is the activator Cr. 3+ Ion doping level, 0.01 at.% ≤ x ≤ 30 at.%.
2. The near-infrared luminescent material according to claim 1, characterized in that, The luminescent material can be excited by blue or red LED chips in the 300-800nm range to emit near-infrared light with a wavelength range of 650-1300nm, with the optimal emission peak at 880nm and a full width at half maximum (FWHM = 160nm). Preferably, A is selected from one, two or more monovalent metal elements such as Na, K, and Li; E is selected from one, two or more divalent metal elements such as Ca, Mg, Sr, and Ba; and M is selected from one, two or more trivalent elements such as Al, Ga, and Sc. Preferably, the chemical composition of the luminescent material can be Na3Mg. 5.49 Si8O 22 F2:0.01Cr 3+ Na3Mg 5.48 Si8O 22 F2:0.02Cr 3+ Na3Mg 5.47 Si8O 22 F2:0.03Cr 3+ Na3Mg 5.46 Si8O 22 F2:0.04Cr 3+ Na3Mg 5.44 Si8O 22 F2:0.06Cr 3 + Na3Mg 5.42 Si8O 22 F2:0.08Cr 3+ Na3Mg 5.40 Si8O 22 F2:0.10Cr 3+ 、Na 2.98 Ca 0.01 Mg 5.44 Al 0.02 Si8O 22 F2:0.03Cr 3+ .
3. The near-infrared luminescent material according to claim 1 or 2, characterized in that, The luminescent material is obtained by heat treatment of raw materials including A source, E source, M source, Si source, F source and Cr source.
4. A method for preparing the luminescent material according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: according to chemical formula A m E n M t Si8O 22 F2:xCr 3+ The stoichiometric ratio of each element in the mixture is determined by mixing the A source, E source, M source, Si source, F source and Cr source, and then heat-treating the mixture to obtain the luminescent material.
5. The preparation method according to claim 4, characterized in that, The A source is provided by a compound containing A ions; for example, it may be selected from one or more of oxides, carbonates and fluorides containing A ions. Preferably, the E source is provided by a compound containing E ions; for example, it may be selected from one or more of oxides, carbonates and fluorides containing E ions. Preferably, the M source is provided by a compound containing M ions; for example, it may be selected from one or more of oxides, carbonates and fluorides containing M ions. Preferably, the Si source is provided by a compound containing Si ions; for example, it may be selected from oxides containing Si ions. Preferably, the F source is provided by a compound containing F ions; for example, it may be a fluoride selected from A, E or M. Preferably, the Cr source is provided by a Cr-containing compound; for example, one of Cr2O3, CrF3, or a combination thereof. Preferably, the preparation method further includes drying the mixed raw materials. For example, the drying temperature is 180–220°C; the drying time is 1–5 hours. Preferably, the heat treatment adopts a two-stage sintering process, wherein the temperature of the first-stage sintering is 400-600℃ and the time of the first-stage sintering is 1-5h; the temperature of the second-stage sintering is 900-1300℃ and the time of the second-stage sintering is 4-10h.
6. The preparation method according to any one of claims 4-5, characterized in that, The steps include: (1) According to chemical formula A m E n M t Si8O 22 F2:xCr 3+ The stoichiometric ratios of each element in the mixture are determined, where 0.01 at.% ≤ x ≤ 30 at.%. Compounds containing A ions, E ions, M ions, Si ions, Cr ions, and F ions are weighed separately and ground to obtain a mixed powder. (2) The mixed powder obtained in step (1) is subjected to heat treatment to obtain the product; (3) The product obtained in step (2) is ground and collected to obtain the luminescent material.
7. Use of the luminescent material according to any one of claims 1-3, as a near-infrared luminescent material, in the fields of detection, marking, identification, and optoelectronic devices using near-infrared light sources; for example, in LEDs.
8. An LED device, characterized in that, It includes at least one luminescent material as described in any one of claims 1-3. Preferably, the LED device further includes an LED chip, the LED chip being used to carry the light-emitting material A according to any one of claims 1-3. m E n M t Si8O 22 F2:xCr 3+ . Preferably, the LED device includes an adhesive layer disposed on the LED chip, the adhesive layer containing uniformly dispersed luminescent material A. m E n M t Si8O 22 F2:xCr 3+ .
9. The method for preparing the LED device according to claim 8, characterized in that, The preparation method includes the following steps: mixing the luminescent material according to any one of claims 1-3 with the adhesive evenly, and then coating it onto the LED chip.
10. The application of the LED device according to claim 8 as a near-infrared light source in the fields of analysis and detection, iris recognition, automotive sensing and security.